Primary plastics of Achilles tendon by plantar muscle tendon for the prevention of repeated ruptures (experimental research) - N. S. Ponomarenko; I. A. Kuklin; N. V. Tishkov; L. A. Zimina; A. V. Semenov; A. P. Zaytsev; A. S. Bubnov (Acta Biomedica Scientifica)
The most important requirement to Achilles tendon suture is its ability to hold loading both in postoperative and. in rehabilitation period. The research was aimed, at the comparison of strength of classic intertendon suture of Achilles tendon and. primary plastics of Achilles tendon by plantar muscle tendon. 60 unfixed (cadaveric) Achilles tendons and 60 plantar muscle tendons were used in experimental research. Further parameters were registered: age, measurements of Achilles and long plantar muscle tendons (length, width, thickness). The first step was to determine the tensile of intact Achilles tendon; the second was to determine the tensile double Polyester N 6 suture; the third — to determine tensile of plantar muscle tendon; the fourth — to determine tensile of Achilles tendon reconstructed with, use of proposed method. As the result of the experiment further conclusions were drawn. 1. Force that causes rupture of Achilles tendon decreases with age of a person that proves degenerative theory of Achilles tendon injury indirectrly. 2. Force that causes rupture of intact Achilles tendon (Ме) is 161,0, of double Polyester N 6 suture — 5,0, of tendon of plantar muscle folded up in four is 22,5; of Achilles tendon reconstructed with use of proposed method is 32,0. 3. Tensile of primary plastics of Achilles tendon sutured with use of proposed method is 6.4 times more than tensile of classic suture (Polyester N 6).